Measurement of comfort variables for occupational footwear in the medical sector - Concha, Alejandra
Currently, health personnel must comply with long working hours of up to 12 hours and during this time many of them have to remain standing or in constant movement. Inadequate footwear for this work can cause health problems and low quality of life, therefore, the objective of this project is to analyze the comfort variables of the footwear currently used by the staff and find their shortcomings, since they are few. studies carried out for this topic, in the health sector. For this, a study of the state of the art was carried out, of the definition of comfort variables, interviews were applied, and measurements were taken of the distribution of plantar pressures in current footwear. Finding that the clogs, the most common footwear, is not the most recommended for this type of work and footwear sketches are proposed that try to solve the shortcomings found.